PENERAPAN PRINSIP-PRINSIP MANAJEMEN KELAS TERHADAP MOTIVASI BELAJAR SISWA DI SD INPRES 6/80 KAWERANG - Ramadhan, Andra; Astuti, Novi; Yusup, Arfandi; Hasbullah, Hasbullah (DIDAKTIKA, 2022)
This study is a qualitative-descriptive research. The aim is to describe the implementation of classroom management principles and explain the impact towards 2nd grade students’ learning motivation in SD Inprees 6/80 Kawerang. the participant of this study are 34 students and 2 teachers. Analytical data technique that used in this study is Interactive data analytic. Based on the analytic, concluded that classroom management in SD Inprees 6/80 Kawerang implemented properly suitable with the classroom management principles, there are: (1) teacher’s gesture like enthusiastic, warmness, and intimateness. (2) challenging learning. (3) various learning activities. (4) teacher’s suppleness in every actions. (5) positivity instruction on the students. (6) discipline instruction on the students. Through classroom management implementation, students become motivated and indicate behaviors like: (1) active in the class. (2) willing to try difficult things. (3) desire to succeeded learning. (4) willing to start from themselves. (5) survive when facing learning difficulties. (6) pay attention to the teacher. Therefore, the conclusion is classroom management principles affected students’ learning motivation.